A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Monasteries - Hamilton-Merritt, Jane (Souvenir Press, 1976)
Keywords: Buddhism; Buddhist meditations; Hamilton-Merritt, Jane; Meditation; dept.his; faculty_collection

A Meditator's Diary: A Western Woman's Unique Experiences in Thailand Temples - Hamilton-Merritt, Jane (Harper & Row, 1976)
Keywords: Buddhism; Hamilton-Merritt, Jane; Meditation; dept.his; faculty_collection

American Pacific Ocean Trade; Its Impact on Foreign Policy and Continental Expansion, 1784-1860 - Caruthers, J. Wade (Exposition-university book, 1973)
Keywords: Commerce; History; History; Pacific Area; History; United States; Pacific Area; United States; dept.his; faculty_collection

Walter Reuther, - Tyler, Robert L. (Great men of Michigan, 1973)
Keywords: Reuther, Walter, 1907-1970; dept.his; faculty_collection

The History of Kenya Agriculture. - Cone, L. Winston; Lipscomb, J. F. (University Press of Africa, 1972)
Keywords: Agriculture; History; Kenya; dept.his; faculty_collection

The Revenge of Heaven; Journal of a Young Chinese. - Ling, Ken; London, Miriam; Lee, Ta-ling (Putnam, 1972)
Keywords: 1949-; China; Politics and government; dept.his; faculty_collection

American Nativism, 1830-1860 - Leonard, Ira M.; Parmet, Robert D. (Anvil original, 1971)
Keywords: 1815-1861; Nativism; Immigrants; Politics and government; United States; United States; dept.his; faculty_collection

The Regulators in North Carolina: A Documentary History, 1759-1776. - Powell, William S.; Huhta, James K.; Farnham, Thomas J. (State Dept. of Archives and History, 1971)
Keywords: History; North Carolina; Regulator Insurrection, 1766-1771; Sources; dept.his; faculty_collection

Africana: Holdings of Books and Other African Resource Material in the Hilton C. Buley Library at Southern Connecticut State College - Southern Connecticut State College Library (Hilton C. Buley Library, Southern Connecticut State College, 1971)
Keywords: Africa; Bibliography; Catalogs; Africa; Connecticut; Library resources; New Haven; dept.his; faculty_collection

Gouverneur Morris and the American Revolution, - Mintz, Max M. (University of Oklahoma Press, 1970)
Report for Bachelor of Engineering (Naval Architecture)., ***CD-ROM held at loans desk***
Keywords: 1775-1783; New York (State); 1775-1783; United States; Biography; Legislators; Biography; United States; Foreign relations; History; Morris, Gouverneur, 1752-1816; Statesmen; Politics and government; Revolution, 1775-1783; dept.his; faculty_collection

Lyautey in Morocco: Protectorate Administration, 1912-1925 - Scham, Alan (University of California Press, 1970)
Keywords: Lyautey, Louis Hubert Gonzalve, 1854-1934; Morocco; Politics and government; dept.his; faculty_collection

Weston: The Forging of a Connecticut Town - Farnham, Thomas J. (Published for the Weston Historical Society by Phoenix Pub., 1979)
Keywords: History; Weston (Conn.); dept.his; faculty_collection

Historians and Slavery: A Critical Analysis of Perspectives and Irony in American Slavery, and Other Recent Works. - Wright, W. D. (1978)
Keywords: Genovese, Eugene D., 1930-2012; Engerman, Stanley L; Perspectives and irony in American slavery; Slavery; Historiography; United States; dept.his; faculty_collection

Urban legacy: the story of America's cities - Klebanow, Diana (Mentor book ; ME1586, 1977)
Keywords: Cities and towns; History; United States; dept.his; faculty_collection

Socio/Psycholinguistics of the cultural revolution: an empirical study - London, Ivan D.; Lee, Ta-Ling (Psychological Reports, 1977)
Keywords: dept.his

Review of Desperate Diplomacy: William H. Seward's Foreign Policy, 1861 - Farnham, Thomas J. (The Journal of Southern History, 1977)
Keywords: dept.his

War and Government in Habsburg Spain, 1560-1620 - Thompson,iaa - Stewart, P (American Historical Review, 1977)
Keywords: dept.his

Book Review: E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35 - Cone, L. Winston (Journal of Asian and African Studies, 1975)
"E. J. Murphy, History of African Civilization. New York, Crowell, 1972, pp. 430, xxlv, maps, plates, $ 14.35" published on 01 Jan 1975 by Brill.
Keywords: book.review; dept.his

Works of Williams,r,sir - Evans,jx - Stewart, P (American Historical Review, 1973)
Keywords: dept.his

Review of The Birth of Modern America, 1820-1850 - Farnham, Thomas J. (The Journal of Southern History, 1972)
Keywords: dept.his

Devaldes,j and Origins of Spanish and Italian Reformation - Spanish - Nieto,jc - Stewart, P (American Historical Review, 1971)
Keywords: dept.his

An eighteenth-century case of plagiarism: william smith's A new voyage to guinea - Feinberg, Harvey M. (History in Africa, 1979)
Keywords: dept.his

Nietzsche and eschatology - Ausmus, Harry J. (The Journal of Religion, 1978)
Keywords: dept.his

Book Review: Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tennessee Press, Tennessee Historical Commission, 1977. 95 pp. Maps, illustrations, more resources, and index. Paper, $3.50.) - Caruthers, J. Wade (Journal of American History, 1978)
J. Wade Caruthers; Visions of Utopia: Nashoba, Rugby, Ruskin, and the “New Communities” in Tennessee's Past. By John Egerton. (Knoxville: University of Tenness
Keywords: book.review; dept.his

Review of The Encyclopaedia Africana Dictionary of African Biography, Volume I: Ethiopia-Ghana - Feinberg, Harvey M. (The International Journal of African Historical Studies, 1978)
Keywords: dept.his

Plant Liberation - Struggle Against Fauna Chauvinism - Tyler, RL (Humanist, 1978)
Keywords: dept.his; ⛔ No DOI found

Review of Trade and Economic Change on the Gold Coast, 1807-1874 - Feinberg, H.M. (The International Journal of African Historical Studies, 1977)
Keywords: dept.his

Schopenhauer's view of history: A note - Ausmus, Harry J. (History and Theory, 1976)
Keywords: dept.his

There Was an Elmina Note, But.... - Feinberg, H.M. (The International Journal of African Historical Studies, 1976)
Keywords: dept.his

Confessions of a Closet Househusband - Tyler, RL (Humanist, 1976)
Keywords: dept.his; ⛔ No DOI found

Review of Akwapim Handbook - Feinberg, H. M. (The International Journal of African Historical Studies, 1975)
Keywords: dept.his

Boredom and Treadmill of Doing - Tyler, RL (Humanist, 1975)
Keywords: dept.his; ⛔ No DOI found

New data on European mortality in West Africa: the Dutch on the Gold Coast, 1719-1760. - Feinberg, Harvey M (The Journal of African History, 1974)
Keywords: dept.his

Review of Colonial Governors from the Fifteenth Century to the Present. A Comprehensive List - Feinberg, H. M. (The International Journal of African Historical Studies, 1973)
Keywords: dept.his

Consciousness Iv - or Let Us Not Envy Young - Tyler, RL (Humanist, 1972)
Keywords: dept.his; ⛔ No DOI found

Old Siwash Is Not Our Beacon - Tyler, RL (Journal of General Education, 1972)
Keywords: dept.his; ⛔ No DOI found

Book Review: Mill town: A social history of everett, washington, from its earliest beginnings on the shores of puget sound to the tragic and infamous event known as the everett massacre. by norman h. clark. (seattle: university of washington press, 1970. x + 267 pp. illustrations, notes, and index. 7.95.) - Tyler, Robert (The Journal of American History, 1972)
Keywords: book.review; dept.his

Review of Benin and the Europeans 1485-1897 - Feinberg, H. M. (African Historical Studies, 1971)
Keywords: dept.his

Review of Trade and Politics on the Gold Coast: 1600-1720. A Study of the African Reaction to European Trade - Feinberg, H. M. (African Historical Studies, 1971)
Keywords: dept.his

Pornos and Prudes Unite - Tyler, RL (Humanist, 1971)
Keywords: dept.his; ⛔ No DOI found

An Incident in Elmina-Dutch Relations, The Gold Coast (Ghana), 1739-1740 - Feinberg, H. M. (African Historical Studies, 1970)
Keywords: dept.his

Review of West African Trade and Coast Society: A Family Study - Feinberg, H. M. (African Historical Studies, 1970)
Keywords: dept.his

2-Marriage Revolving-Mate Generation-Bridging Plan to Save Marriage - Tyler, RL (Humanist, 1970)
Keywords: dept.his; ⛔ No DOI found